Wills & trusts kit - Larson, Aaron (--For dummies., 2021)
Regardless of your age or income, writing a legal will is one of the greatest gifts you can give your family. But where do you begin? Wills & Trusts Kit For Dummies walks you through the most important considerations to have in mind when you're deciding what will happen to your estate when you're gone.